2020
DOI: 10.34067/kid.0002652020
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Associated with Coronavirus Disease 2019 in Urban New Orleans

Abstract: BackgroundAKI is a manifestation of COVID-19 (CoV-AKI). However, there is paucity of data from the United States, particularly from a predominantly black population. We report the phenotype and outcomes of AKI at an academic hospital in New Orleans.MethodsWe conducted an observational study in patients hospitalized at Ochsner Medical Center over a 1-month period with COVID-19 and diagnosis of AKI (KDIGO). We examined the rates of RRT and in-hospital mortality as outcome measures.ResultsAmong 575 admissions (70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
243
7
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(281 citation statements)
references
References 25 publications
24
243
7
7
Order By: Relevance
“…In comparison, the mortality rates in COVID-19 hospitalized patients without AKI are in most cases much lower, around 6%. Finally, consistent with observations of increased COVID-19 morbidity and mortality in minorities, the studies of Zahid et al [5] and Mohamed et al [8] also demonstrate that AKI in minorities with COVID-19 is more severe and associated with an increased mortality compared to non-minority populations.…”
Section: Tablesupporting
confidence: 84%
See 1 more Smart Citation
“…In comparison, the mortality rates in COVID-19 hospitalized patients without AKI are in most cases much lower, around 6%. Finally, consistent with observations of increased COVID-19 morbidity and mortality in minorities, the studies of Zahid et al [5] and Mohamed et al [8] also demonstrate that AKI in minorities with COVID-19 is more severe and associated with an increased mortality compared to non-minority populations.…”
Section: Tablesupporting
confidence: 84%
“…In COVID-19 patients admitted to the ICU, the incidence of AKI is even greater, ranging from 61 to 76%. Second, AKI in COVID-19 patients is frequently severe – 31–66% of AKI patients have Stage 3 AKI, and 14–55% of cases require RRT, although the 55% observation is an outlier for unclear reasons [8]. In addition, 19–34% of ventilated patients required RRT.…”
Section: Tablementioning
confidence: 99%
“…We found the incidence of AKI in COVID-19 patients was more than double the incidence of AKI in non-COVID-19 patients. The incidence of AKI in COVID-19 in our study is similar to that reported from the United States of America (22.2% to 36%) but much higher than that reported from China (5.1% to 10.5%) [ 1 , 2 , 6 , 7 , 15 , 16 ]. The variation in the incidence of AKI in COVID-19 in different countries or regions may be explained in part by variable inclusion criteria (intensive care and all hospital admissions) and also the varying demographic characteristics and comorbidities of study populations.…”
Section: Discussionsupporting
confidence: 91%
“…Large variation has been reported in the prevalence of comorbidities in patients with COVID-19 and AKI. For example, we observed that diabetes was present in 25% of patients with COVID-19 and AKI, whereas the proportion with diabetes in studies from the US has been reported as 41% to 47% and from China as 14% [ 5 , 6 , 15 ]. We did not identify diabetes as risk factor for AKI or mortality in contrast to a study from the US [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation